Cyclone–anticyclone asymmetry in rotating thin fluid layers. Issue 4 (4th May 2021) - Boffetta, G.; Toselli, F.; Manfrin, M.; Musacchio, S.
Abstract : We report of a series of laboratory experiments and numerical simulations of freely decaying rotating turbulent flows confined in domains with variable height. We show that the vertical confinement has important effects on the formation of large-scale columnar vortices, the hallmark of rotating turbulence, and in particular delays the development of the cyclone–anticyclone asymmetry. We compare the experimental and numerical results face-to-face, showing the robustness of the results.